Studies on Non-synonymous Polymorphisms Altering Human DNA Topoisomerase II-Alpha Interaction with Amsacrine and Mitoxantrone: An In Silico Approach - Farsani, Farzaneh M.; Ganjalikhany, Mohamad Reza; Vallian, Sadeq (Current Cancer Drug Targets, 2017)
Background: DNA topoisomerase II-α (Top2-α), an essential enzyme for the management of DNA during replication, transcription, recombination, and chromatin remodeling, is one of the most important anticancer targets. Numerous molecules have been designed as Top2-α inhibitors. However, several studies have shown that polymorphisms and mutations in Top2 have conferred resistance to most of these anticancer drugs. The aim of this study was to computationally examine the mechanisms by which genomic variations in Top2-α could affect its resistance to Amsacrine and Mitoxantrone as important inhibitors of the enzyme. Results: The results showed that variants K529E, R568H, R568G and T530M could affect Top2-α inhibition by Amsacrine causing possible drug-resistant. Moreover, R487K, and Y481C variants could change the response of the enzyme to Mitoxantrone. Conclusion: These results could facilitate the prediction and development of more effective drugs for Top2-α variants, making the cancer chemotherapy more effectiv
Keywords: docking